(untitled) (Ustozlar uchun, 2025)
The Brontë Sisters: Innovators of the Victorian Novel explores the literary contributions of Charlotte, Emily, and Anne Brontë, highlighting their revolutionary impact on 19th-century fiction. The study examines how their novels challenged Victorian social norms through intense emotional depth, strong female protagonists, and innovative narrative techniques. The Brontë sisters reshaped the Victorian novel by blending realism with romanticism and psychological insight, leaving a lasting influence on English literature.